Exploring the legal challenges of complying with overlapping international obligations related to public procurement review mechanisms: case-studies of Armenia and Kazakhstan - Solomonyan, Astghik (2020)
The creation of the World Trade Organisation did not end the practice of signing regional trade agreements with states demonstrating a preference for regionalism over multilateralism. Fragmentation of international trade law and public procurement regulation brought by proliferation of regional trade agreements is a reality and a potential source of conflict of norms. Reflecting on the theory of fragmentation of international trade law in general and public procurement regulation in particular, this thesis analyses procurement review mechanisms found in multiple international trade agreements signed by two countries, namely Armenia and Kazakhstan. The World Trade Organisation Agreement on Government Procurement (GPA), the Eurasian Economic Union Treaty covering 5 post-Soviet states and the most recent EU bilateral agreements with Armenia and Kazakhstan are examined in order to reveal instances of conflict of norms involving procurement review mechanisms. The analysis of the relevant agreements is based on the study of geopolitical realities of both countries, which can have an impact on their international obligations. Horizontal comparative analysis is conducted to identify cases of conflict of norms among the provisions of the mentioned four trade agreements related to procurement review mechanisms. Through vertical comparative analysis, the compliance of the national legislation of Armenia and Kazakhstan with the requirements of the relevant trade agreements is examined. The thesis reveals that the multiplicity of international treaties can indeed have a negative impact on the simultaneous compliance with (conflicting) international obligations by Armenia and Kazakhstan.